2018
DOI: 10.1670/17-157
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Occupancy and Detectability of Toad Headed Agamas at the Periphery of Their Range in Mongolia

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Among reptiles recorded in Mongolia (and in this study), the Tuvan Toad-headed Agama (Phrynocephalus versicolor) is the most abundant and widely distributed reptile in the semi-desert and desert regions of Mongolia (Terbish et al 2006b). Similarly, Yadamsuren et al (2018) emphasized that this species might represent the most abundant vertebrate in some parts of Mongolia (see also Murdoch et al 2010). Our surveys indicated that it is the most common herpetofaunal species in northwestern Mongolia (40 individuals recorded at four of six sites).…”
Section: Moorfrogmentioning
confidence: 95%
“…Among reptiles recorded in Mongolia (and in this study), the Tuvan Toad-headed Agama (Phrynocephalus versicolor) is the most abundant and widely distributed reptile in the semi-desert and desert regions of Mongolia (Terbish et al 2006b). Similarly, Yadamsuren et al (2018) emphasized that this species might represent the most abundant vertebrate in some parts of Mongolia (see also Murdoch et al 2010). Our surveys indicated that it is the most common herpetofaunal species in northwestern Mongolia (40 individuals recorded at four of six sites).…”
Section: Moorfrogmentioning
confidence: 95%